Status of Implementation of Corruption Criminal Offices Related to State Financial Loss in Soe Subsidiaries - Khoirul Anwar; Muhammad Salman Alfarisi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose and objective of this legal research is to identify the principles and principles of a rule of law as well as the concepts used to examine how the implementation of the Special Offenses for Criminal Acts of Corruption which ensnares the leadership of a subsidiary of a state-owned company in the form of a Persero. This type of legal research is normative, using a statutory approach and also using a comparative approach. The results of this study indicate that the losses suffered by subsidiaries are not state losses and the application of criminal acts of corruption to the leadership of SOE subsidiaries is irrelevant.